2013
DOI: 10.1103/physrevb.87.220201
|View full text |Cite
|
Sign up to set email alerts
|

Extracting thermodynamic behavior of spin glasses from the overlap function

Abstract: The nature of equilibrium states in disordered materials is often studied using an overlap function P (q), the probability of two configurations having similarity q. Exact sampling simulations of a two-dimensional proxy for three-dimensional spin glasses indicate that common measures of P (q) in smaller samples do not decide between theoretical pictures. Strong corrections result from P (q) being an average over many scales, as seen in a toy droplet model. However, the medianĨ (q) of the integrals of sample-de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…(11) and (12) below, is predicted to be nonzero in the vicinity of q = 0 as the size of the system N ≡ L d tends to infinity according to RSB theory, 3 whereas it is expected to vanish 5 as L −θ in the droplet picture where θ is a positive "stiffness" exponent. Results from simulations [12][13][14][15] seem close to the predictions of RSB, but it has been argued 16,17 that the sizes which can be simulated are too small to see the asymptotic behavior.…”
Section: Introductionmentioning
confidence: 72%
“…(11) and (12) below, is predicted to be nonzero in the vicinity of q = 0 as the size of the system N ≡ L d tends to infinity according to RSB theory, 3 whereas it is expected to vanish 5 as L −θ in the droplet picture where θ is a positive "stiffness" exponent. Results from simulations [12][13][14][15] seem close to the predictions of RSB, but it has been argued 16,17 that the sizes which can be simulated are too small to see the asymptotic behavior.…”
Section: Introductionmentioning
confidence: 72%
“…It was found that P (q) J > 0 if −q EA < q < q EA . For more realistic spin glass models with short range interactions, basically different results have been reported by Newman and Stein [272], Middleton [273], Billoire et al [274] who studied the averaged overlap probability distribution. The differences are related to the number of energy valleys, the consequences of spatial structure and the absence/presence of frustration.…”
Section: Effects Of Randomnessmentioning
confidence: 85%
“…To leading order without finite-size corrections, domain walls appear to be fractals and the weights near zero overlap is finite [7,8,11,14] for the system sizes currently accessible. New statistics or finitesize corrections are therefore intensively developed, and point to different scenarios [20,23,[41][42][43].…”
Section: Introductionmentioning
confidence: 99%